The role of ERM and corporate governance in managing COVID-19 impacts: SMEs perspective - Monika Wieczorek-Kosmala; Thomas Henschel (Journal of Risk and Financial Management, 2022)
SMEs are perceived as more exposed to the consequences of external shocks. The purpose of our work is to examine whether the ERM sophistication or corporate governance mechanisms could be relevant in resistance to COVID-19 shock in the SMEs. In particular, we hypothesize that the SMEs with greater degree of ERM sophistication and stronger CG mechanisms will have a clearer understanding about the severity of the impacts from COVID-19. Our empirical evidence is based on the results of a survey conducted within a large sample of SMEs operating in Poland and in Germany within different experimental settings. We have found that the ERM and CG sophistication influence the perception of COVID-19 interruptions and will alert companies to adjust their business strategy and organizational structure to better cope with effects of the current crisis. The proposed framework can also be a valuable tool for consultants to use to enhance the ERM systems in SMEs.
Keywords: 650; COVID-19; SMEs; corporate governance; ERM